Governance in Malawian universities: The role of dialectical reasoning and communicative rationality - Shawa, Lester Brian (South African Journal of Higher Education, 2016)
Contrary to much research that describe governance problems in African universities within lenses of positivism, this paper takes a critical theory approach. Based on insights from in-depth interviews with university administrators, academics and student union leaders, the paper reveals tensions among these university actors, which stem from the neopatrimonial aspect of the big-man syndrome. The big-man syndrome poses as the taken-for-granted aspect that facilitates misuse of power among university actors. Thus, this paper demonstrates that in Malawian universities most governance problems result from misuse of power among actors facilitated by the big-man syndrome. A proposal presented is for actors to contain the big-man syndrome and allow for democratic governance by employing dialectical reasoning and the Habermasian theory of communicative rationality. Keywords: university governance, critical theory, the big-man syndrome, democratic governance, dialectical reasoning, communicative rationality